The Physician as Captain of the Ship
XV, 256 p.
Keywords: "The fixed person for fixed duties, who in older societies was such a godsend, in the future ill be a public danger." Twenty years ago, a single legal metaphor accurately captured the role that American society accorded to physicians. The physician was "c- tain of the ship." Physicians were in charge of the clinic, the Operating room, and the health care team, responsible - and held accountabl- for all that happened within the scope of their supervision. This grant of responsibility carried with it a corresponding grant of authority; like the ship's captain, the physician was answerable to no one regarding the practice of his art. However compelling the metaphor, few would disagree that the mandate accorded to the medical profession by society is changing. As a result of pressures from a number of diverse directions - including technological advances, the development of new health professionals, changes in health care financing and delivery, the recent emphasis on consumer choice and patients' rights - what our society expects phy- cians to do and to be is different now. The purpose of this volume is to examine and evaluate the conceptual foundations and the moral imp- cations of that difference. Each of the twelve essays of this volume assesses the current and future validity of the "captain of the ship" metaphor from a different perspective. The essays are grouped into four sections. In Section I, Russell Maulitz explores the physician's role historically.